Thirty Years of the Drug Candidate NAMI‐A and the Myths in the Field of Ruthenium Anticancer Compounds: A Personal Perspective - Alessio, Enzo (European journal of inorganic chemistry, 2017)
As anticipated in the title, this contribution is basically divided into two, strictly connected, parts. The first is a personal overview of the ruthenium drug candidate NAMI‐A, almost 30 years after its synthesis and the discovery of its unprecedented antimetastatic properties in animal models at nontoxic dosages. The sections relating to the chemical and biological behavior of the complex, and the hypotheses on its mechanism(s) of action, are kept to a minimum, whereas more space is devoted to discussion of the results of the clinical investigations. The second part deals in detail with a number of undemonstrated misconceptions (or myths) that, over the years, have thrived around NAMI‐A and other ruthenium drug candidates, thus negatively affecting the whole field of Ru anticancer drugs. Almost 30 years after the discovery of NAMI‐A, and after two clinical phase studies have been accomplished, the time seems to be appropriate for drawing up a balance sheet. The undemonstrated misconceptions (or myths) that, over the years, have thrived around NAMI‐A and other ruthenium drug candidates are also critically addressed in detail.